Good hunting an American spymaster's story - Devine, Jack; Loeb, Vernon (Sarah Crichton Books, 2014)
A master class in spycraft from one of its greatest practitioners. Jack Devine is one of the legendary spymasters of our time. Its capacity to do what it does best has been seriously degraded. In wonderfully readable prose, Good Hunting aims to set the record straight. This is a revelatory inside look at an organization whose history has not been given its real due.